Humble inquiry : the gentle art of asking instead of telling - Schein, Edgar H. (San Francisco : Berrett-Koehler Publishers, Inc., 2013)
"We live, says Ed Schein, in a culture of Tell. Rather than trying to genuinely relate to other people we tell them what we think they need to know or should do based on assumptions we've made about them. But telling makes people feel inferior--it shuts them down. This is particularly true of interactions between superiors and subordinates, and that's where it's particularly problematic. In today's complex, interconnected, rapidly changing world hierarchy means nothing--anybody anywhere could have that vital fact or insight that could mean the difference between success or disaster. A free flow of information is crucial. Humble Inquiry builds the kinds of positive, trusting, balanced relationships that encourage honest and open interactions in both our professional and personal lives. Schein defines Humble Inquiry as "the fine art of drawing someone out, of asking questions to which you do not know the answer, of building a relationship based on curiosity and interest in the other person." In this seminal work he explores the concept of humility, looks at how Humble Inquiry differs from other kinds of inquiry, offers examples of Humble Inquiry in action in many different settings, and shows how to overcome the cultural, organizational and psychological barriers that keep us from practicing it. This is a major new contribution to how we see human dynamics and relationships, presented in a compact, personal, eminently practical way"--
"From one of the true giants in organizational development, career development and organizational psychology comes a simple and effective technique for building more positive relationships--particularly between people of different status--that will lead to more honest and open interactions and stronger organizations"--
Humble inquiry -- Humble inquiry in practice: case examples -- Differentiating humble inquiry from other kinds of inquiry -- The culture of do and tell -- Status, rank and role boundaries as inhibitors -- Forces inside us as inhibitors -- Developing the attitude of humble inquiry.
Includes bibliographical references and index.
Keywords: Interpersonal communication; Interpersonal relations; Organizational behavior; Humility